2006
DOI: 10.1139/y06-015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of astragaloside IV on diabetic peripheral neuropathy in rats

Abstract: Astragaloside IV (AGS-IV), a new glycoside of cycloartane-type triterpene isolated from the root of Astragalus membranaceus (Fisch.) Bunge, has been used experimentally for its potent immune-stimulating, anti-inflammatory, and antioxidative actions. A recent study has shown AGS-IV to be an aldose-reductase inhibitor and a free-radical scavenger. This study examined the effects of AGS-IV on motor nerve conduction velocity (MNCV), tailflick threshold temperature, biochemical indexes, and the histology of the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 32 publications
2
71
1
Order By: Relevance
“…Traditionally, AR was used to treat weakness, wounds, anemia, fever, multiple allergies, chronic fatigue, loss of appetite, uterine bleeding, and uterine prolapse . Medicinally, AR is used as a diuretic and tonic herb in many Asian countries, to enhance physical strength and endurance, strengthen the immune system, lower blood pressure, and promote excretion and circulation (Zhao et al, 1990;Sheng et al, 2001;Yu et al, 2006). Clinically, AR is used to treat chronic phlegmatic disorders and general gastrointestinal disturbances including stomach ulcers and diarrhea (Yang, 1993;Hei et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, AR was used to treat weakness, wounds, anemia, fever, multiple allergies, chronic fatigue, loss of appetite, uterine bleeding, and uterine prolapse . Medicinally, AR is used as a diuretic and tonic herb in many Asian countries, to enhance physical strength and endurance, strengthen the immune system, lower blood pressure, and promote excretion and circulation (Zhao et al, 1990;Sheng et al, 2001;Yu et al, 2006). Clinically, AR is used to treat chronic phlegmatic disorders and general gastrointestinal disturbances including stomach ulcers and diarrhea (Yang, 1993;Hei et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…AS-IV, an active monomer of Astragalus membranaceus, has been suggested to have a potentially protective role in various disorders [13][14][15][16][17], with immunoregulatory and anti-inflammatory functions [36,37]. Noticeablely, DU et al [17] have reported that AS-IV suppressed the progression of airway inflammation, airway hyperresponsiveness and airway remodelling (goblet cell hyperplasiain and subepithelial fibrosis) in a ovalbumin-induced murine model of chronic asthma, indicating the protective effects of AS-IV on airway inflammatory injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, astragaloside IV (AS-IV) is a new glycoside of cycloartane-type triterpene isolated from the root of Astragalus membranaceus Bunge, a Chinese medicinal herb, which has been reported to have protective effects on various animal and in vitro disease models [13][14][15][16][17]. As the effect of AS-IV on CS-induced airway inflammation is not clear, the investigation of the effect of AS-IV on this process was also performed in this study.…”
mentioning
confidence: 99%
“…Bunge, is one of the most widely used plant-derived drugs in traditional Chinese medicine for diabetes therapy (10). The saponin astragaloside IV has been reported to exert various pharmacological effects; astragaloside IV inhibited hepatic glycogen phosphorylase (GP) and glucose-6-phosphatase (G6P) activities thereby decreasing serum glucose levels in diabetic mice (12), attenuated lipolysis and reduced insulin resistance induced by tumor necrosis factor α (TNFα) in 3T3-L1 adipocytes (13), improved the symptoms of metabolic syndrome in fructose-fed rats (14), prevented human cardio vascular pathological changes and protected against cardiovascular injury in rats (15)(16)(17)(18) improved renal function (19)(20)(21)(22), reduced the progression of peripheral neuropathy (23), and attenuated inflammatory responses by suppressing the nuclear factor-κB (NF-κB) pathway (24)(25)(26). Xu et al (27) reported that other astragalosides, astragaloside II and isoastragaloside I, elevated serum levels of adiponectin and alleviated insulin resistance and glucose intolerance in obese mice.…”
Section: Introductionmentioning
confidence: 99%